If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + 7) + y = 3(y + 2) + -8 Reorder the terms: 6(7 + y) + y = 3(y + 2) + -8 (7 * 6 + y * 6) + y = 3(y + 2) + -8 (42 + 6y) + y = 3(y + 2) + -8 Combine like terms: 6y + y = 7y 42 + 7y = 3(y + 2) + -8 Reorder the terms: 42 + 7y = 3(2 + y) + -8 42 + 7y = (2 * 3 + y * 3) + -8 42 + 7y = (6 + 3y) + -8 Reorder the terms: 42 + 7y = 6 + -8 + 3y Combine like terms: 6 + -8 = -2 42 + 7y = -2 + 3y Solving 42 + 7y = -2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 42 + 7y + -3y = -2 + 3y + -3y Combine like terms: 7y + -3y = 4y 42 + 4y = -2 + 3y + -3y Combine like terms: 3y + -3y = 0 42 + 4y = -2 + 0 42 + 4y = -2 Add '-42' to each side of the equation. 42 + -42 + 4y = -2 + -42 Combine like terms: 42 + -42 = 0 0 + 4y = -2 + -42 4y = -2 + -42 Combine like terms: -2 + -42 = -44 4y = -44 Divide each side by '4'. y = -11 Simplifying y = -11
| 7x-8y=13findy | | 3x+9y=-24 | | 2ab-7b-5ab-6b= | | 7x-8y=13 | | 3x+4+5x-6=180 | | 8-3(x+2)=7 | | 2(x-7)+4=8 | | 6=6+n | | 2+4x=5x-1 | | 15+(3x-6)=(9+x)2 | | -6.5=-4.3-n | | 5x+1-5x=8 | | x/(-6)=-14 | | x^2-28X+180=y | | (x/4)+3x/2=3/8 | | 8x-19=19+11x | | -6x+2y=-5 | | x/4+3x/2=3/8 | | -5y+21=36 | | 5(5x-2)+3=-1 | | 5x-1x=15-x | | 7(x-6)+28=-21 | | 4x+(4-4x)=4 | | x/21=-3 | | -144=-6k | | 6(6-5)+36-7= | | -1x+8=-7x+2 | | -1x+8=7x+2 | | x+3+-2=10 | | 1/2(2p+1)-(3p+2)=3/4 | | 14m+3n-4m+10n= | | -144=6k |